STRATEGI PENDIDIKAN ISLAM DALAM MENINGKATKAN KUALITAS SUMBER DAYA MANUSIA - Ruma Mubarok (el-hikmah, 2012)
The reality of Islamic Education today has experienced a period of intellectual deadlock. Among the indications; first, the lack of reform efforts, and if there is certainly less rapidly with changes in social, political and progress of science and technology. Second, the practice of Islamic education still maintains the old heritage and did not do much creative thinking, innovative and critical current issues. Third, the model of Islamic education learning too much emphasis on intellectualism-verbalistic approach and negate the importance of educational interaction and humanistic communication between the teacher and student. Fourth, Islamic education orientation focuses on the formation ‘abd or slave and disproportionate to the achievement of human character as a Muslim caliph on the earth. On the other hand, Islamic education is an important task, namely how to develop the quality of human resources (HR) for Muslim to take an active role and to survive in the era of globalization. The development of quality human resources is not an easy issue and simple, as it requires deep understanding and broad at the formation of the basic concepts of man and calculation in the preparation of the institution as a device that will give birth to a superior human.